2020
DOI: 10.1159/000511265
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Optical Coherence Tomography Angiography for Choroidal Neovascularization in Age-Related Macular Degeneration: A Systematic Review and Meta-Analysis

Abstract: Objective: To evaluate the diagnostic value of optical coherence tomography angiography (OCTA) in detecting the choroidal neovascularization (CNV) in agerelated macular degeneration (AMD). Methods: A systematic review and meta-analysis was performed by searching Pubmed, Science Direct, Embase and Web of Science. The pooled sensitivity and specificity with 95% confidence intervals (CIs), area under the summary receiver operator characteristic curve (sROC), and the total accurate classification rate were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…OCTA helps observe the relevant vascular distributions without bringing any side effects to the eyes. By following the microvascular structures at different retina layers, OCTA extracts the microvascular system distributed in the accessory fovea, and thus, could be applied for the early diagnosis of retinal diseases, such as age‐related macular degeneration (AMD) [3], diabetic retinopathy [4], artery and vein occlusions [5], and glaucoma [6]. Furthermore, recent studies also have shown that the retinal microvascular morphological changes revealed by OCTA are related to Alzheimer's disease and mild cognitive impairment (MCI) [7].…”
Section: Introductionmentioning
confidence: 99%
“…OCTA helps observe the relevant vascular distributions without bringing any side effects to the eyes. By following the microvascular structures at different retina layers, OCTA extracts the microvascular system distributed in the accessory fovea, and thus, could be applied for the early diagnosis of retinal diseases, such as age‐related macular degeneration (AMD) [3], diabetic retinopathy [4], artery and vein occlusions [5], and glaucoma [6]. Furthermore, recent studies also have shown that the retinal microvascular morphological changes revealed by OCTA are related to Alzheimer's disease and mild cognitive impairment (MCI) [7].…”
Section: Introductionmentioning
confidence: 99%